2016
DOI: 10.1016/j.jor.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Short-term evaluation of arthroscopic outside-in repair of ulnar side TFCC tear with vertical mattress suture

Abstract: a b s t r a c tBackground: There has been controversy regarding the pathogenesis and treatment of TFCC tear. Different surgical techniques for the treatment of TFCC are prescribed. The purpose of this study was to evaluate the short-term outcomes of arthroscopic outside-in repair of the ulnar side TFCC tear with vertical mattress suture. Methods:In this study, arthroscopic outside-in repair of the ulnar side TFCC tear was done.37 patients with TFCC tear with failure of conservative treatment for a minimum of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 11 publications
2
32
0
Order By: Relevance
“…8 Regarding arthroscopic treatment of peripheral tears, PRWE scores ranging from 19 to 33 with a follow-up range of 11.5 to 17.5 months have been reported. 11,21 These PRWE scores described are comparable to our median PRWE of 19.5, concluding that arthroscopic treatment of TFCC lesions leads to acceptable functional outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…8 Regarding arthroscopic treatment of peripheral tears, PRWE scores ranging from 19 to 33 with a follow-up range of 11.5 to 17.5 months have been reported. 11,21 These PRWE scores described are comparable to our median PRWE of 19.5, concluding that arthroscopic treatment of TFCC lesions leads to acceptable functional outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…11,14,15,[26][27][28][29][30] Arthroscopic-assisted techniques have shown good results at follow-up ranging from 11 months to 4.8 years with pain reduction by VAS, grip strength returning to a mean of 71 to 95% of the contralateral hand, near full wrist and forearm motion, and improved outcome scores with mean DASH, PRWE, and MMW scores of 9 to 22, 33, and 71 to 91, respectively. 11,14,15,[26][27][28][29][31][32][33][34][35][36] All-arthroscopic techniques are performed solely through the arthroscopic portals and knots are placed intra-articularly. 30 Few studies have reported on outcomes following allarthroscopic repair of Palmer 1B peripheral TFCC tears.…”
Section: Discussionmentioning
confidence: 99%
“…9 Tang et al, 10 Kim et al, 11 Sarkissian et al, 12 and Iwasaki et al 13 all moved to surgery after 3 months with Iwasaki et al using a removal wrist brace for immobilization. Ruch and Papadonikolakis 14 and Infanger and Grimm 15 proceeded after at least 4 months of conservative management and Papapetropoulos et al, 16 Bayoumy et al, 17 and Millants et al 18 utilized 6 months of conservative management with splinting and anti-inflammatories prior to surgical intervention.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…In our review, 16 articles were found focusing specifically on outcomes of arthroscopically repaired 1B lesions with a total of 409 patients undergoing repair. [11][12][13][16][17][18][38][39][40][41][42][43][44][45][46][47] For the 16 articles, four different scoring metrics were reported (Disabilities of the Arm, Shoulder, and Hand [DASH], Mayo, visual analog scale, and personal scoring system) and not every article reported pre-and postoperative values. Additionally, not all reported range of motion (ROM), pain, or return to work status.…”
Section: Repairmentioning
confidence: 99%
See 1 more Smart Citation